Borehole logging data, P-wave velocity of sediment core GeoB22605-1 - Tim Freudenthal (PANGAEA, 2020)
LLogging was performed with the sea floor drill rig MARUM-MeBo200 in a borehole drilled with a 103 mm diameter bit. The 1343 Slimhole Memory Acoustic instrument developed by ANTARES Datasystems GmbH was used. The probe consists of 1 transmitter and two receivers in 0.9 and 1.0 m distance, respectively. Sound velocity in the formation was calculated from the time difference of signal arrival at both receivers using the waveform processing module of the Antares software GeoBase 6.22. The vertical resolution is about 10 cm. The accuracy is better than 10 m/s.